Discontinuous Mixed Covolume Methods for Parabolic Problems - Ailing Zhu; Ziwen Jiang (The Scientific World Journal)
We present the semidiscrete and the backward Euler fully discrete discontinuous mixed covolume schemes for parabolic problems on triangular meshes. We give the error analysis of the discontinuous mixed covolume schemes and obtain optimal order error estimates in discontinuous Hdiv and first-order error estimate in L2.